The jailhouse divergence: Why debtors’ prisons disappeared in 19th century Europe and flourished in West Africa - Balakrishnan, Sarah (Punishment & society, 2022)
It has been argued that the debtors’ prison was abolished in 19th century Europe and North America because the institution contradicted the principles of modern capitalism; by confining debtors for unpaid loans, it punished the poor while hampering the creditor, who could not be repaid by a debtor rotting in jail. This essay revises these assumptions through a study of debtors’ prisons in 19th century Ghana. It argues that, in both Europe and West Africa, the debtors’ prison historically emerged as a hostage-taking institution. Families paid their members’ loans to free them. In 19th century Ghana, this system proved crucial to the spread of mercantile capitalism; debt inmates were released within a week and creditors were repaid in full. However, in Euro-America, a new belief in homo economicus as the ‘self-made man’ portrayed insolvency as an individual failure. The European nuclear family also reduced the financial base supporting the debtor. The result was that debtors faced months, if not years, behind bars. This essay suggests that debtors’ prisons disappeared in Europe, while flourishing in West Africa, not due to the emergence of capitalism, but because of the social fabric of credit relations—the financial obligations of Africa kin networks versus European families.